Compositions containing poly(arylene ether sulfone)s
The composition of polyarylene (ether)sulfone with graphite, conductive carbon black, and carbon nanotubes addresses the limitations of existing polymeric materials in bipolar plates, offering improved mechanical and electrical performance, as well as enhanced chemical and thermal resistance.
Patent Information
- Application Number
- JP2024555201
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-18
- Filing Date
- 2023-03-10
- Publication Date
- 2025-04-11
AI Technical Summary
Existing polymeric materials used in bipolar plates for fuel cells suffer from poor toughness, insufficient heat resistance, and brittleness, which limits their applicability and durability.
A composition comprising at least one polyarylene (ether)sulfone with a viscosity number of 15-90% by weight, combined with 5-80% by weight graphite, 5-80% by weight conductive carbon black, 0-25% by weight carbon nanotubes, and 0-40% by weight additives, which enhances mechanical performance and electrical conductivity.
The composition achieves excellent mechanical properties, high electrical conductivity, good chemical resistance, thermal conductivity, and improved processability, making it suitable for manufacturing bipolar plates with enhanced performance and durability.
Smart Images

Figure 2025509777000001 
Figure 2025509777000002 
Figure 2025509777000003
Abstract
Description
[Technical field]
[0001] The present invention relates to compositions comprising polyarylene (ether) sulfones having high electrical conductivity, good chemical resistance and improved processability suitable for use in the manufacture of bipolar plates for fuel cells or electrolysis units. [Background technology]
[0002] Bipolar plates are an essential component of a fuel cell. They provide electrical conductivity and connect the multiple cells in a stack. In addition, they provide the flow field for uniform distribution of hydrogen and oxygen to the Membrane Electrode Assembly (MEA). To ensure a constant operating temperature, a coolant is usually circulated in the system. In addition to electrical conductivity, the thermal conductivity of the plates is therefore also important.
[0003] In practice, various materials are used to prepare bipolar plates. Metals exhibit good mechanical stability and low gas permeability, but the preparation of a huge number of plates is very difficult. In addition, after a long operating time, metal plates are subject to corrosion.
[0004] Resins filled with large amounts of carbon-based conductive additives such as carbon black, graphite, carbon fiber, carbon nanotubes, graphene, etc. have good electrical conductivity and low gas permeability, but low toughness, which can lead to plate breakage during assembly or operation of the fuel cell stack.
[0005] Highly filled compounds based on a thermoplastic matrix and carbon-based additives are also used as materials for manufacturing bipolar plates. In fuel cells operating below 80°C, polypropylene-based compounds may be used, but at higher operating temperatures polymers with a higher modulus at T>80°C must be used (RA Antunes, J. Power Sources 196, 2011, 2945; FGB San, Int. J. Energy Research 37, 2013, 283).
[0006] PPS (polyphenylene sulfide) is widely used as a matrix for highly conductive compounds (S. Radhakrischnan, J. Power Sources 163, 2007, p. 702). Beside the many advantages of PPS, these compounds are very brittle and plates made with such compounds tend to break already during fabrication. [Prior art documents] [Non-patent literature]
[0007] [Non-Patent Document 1] RAAntunes, J.Power Sources 196, 2011, page 2945 [Non-Patent Document 2] FGBSan, Int.J.Energy Research 37, 2013, 283 pages [Non-Patent Document 3] S. Radhakrishnan, J. Power Sources 163, 2007, p. 702 Summary of the Invention [Problem to be solved by the invention]
[0008] Thus, commonly used polymeric materials often exhibit insufficient toughness and poor heat resistance, limiting their applicability in bipolar plates.The problem underlying the present invention was therefore to address the shortcomings of known polymeric materials and to provide compositions that are particularly suitable for use in bipolar plates.Furthermore, the object of the present invention was to provide new compounds or compositions that can be processed using established processing techniques, such as injection molding, extrusion or melt pressing, into highly conductive objects that exhibit good mechanical performance, such as plates useful in fuel cell or electrolysis applications. [Means for solving the problem]
[0009] This problem has been solved by the composition of the present invention. In particular, the present invention provides A) 15 to 90% by weight of at least one polyarylene (ether) sulfone having a viscosity number of less than 42 ml / g; B) 5 to 80 weight percent graphite; C) 5 to 80% by weight of conductive carbon black; D) 0 to 25% by weight of carbon nanotubes; E) 0 to 40% by weight of at least one additive; A composition comprising: A composition is provided, wherein the sum of the weight percent of the components of the composition is 100 weight percent.
[0010] As used herein, "at least one" may generally mean one or more than one, e.g., three or four or five or more, and more may mean multiple or uncounted. For example, it may mean a mixture of one or more than one. When used in relation to chemical compounds, "at least one" is intended to describe one or more chemical compounds that differ in their chemical makeup, i.e., chemical properties.
[0011] Furthermore, in this specification, "polymer" may mean a homopolymer or a copolymer, or a mixture thereof. Those skilled in the art recognize that any polymer may be essentially homopolymeric or copolymeric, but is typically a mixture of polymeric individuals differing in composition, such as chain length, degree of branching, or nature of the end groups. Thus, hereinafter, "at least one" as a prefix to a polymer means that different types of polymers may be included, whereby each type may have differences in the composition described above.
[0012] The composition of the present invention comprises 15-90% by weight of at least one polyarylene(ether)sulfone (component A)) having a viscosity number (Viscosity Number: VN) of less than 42 ml / g. The viscosity number is measured according to ISO 1628 in NMP (N-methyl-2-pyrrolidone) at a concentration of 1 g per 100 ml of solution at 25° C. The VN is a general parameter in the field of polymers that correlates with the molecular weight of the respective material. This parameter is well known to those skilled in the art.
[0013] Polyarylene (ether) sulfones belong to a group of high temperature resistant polymers that exhibit high heat resistance, excellent mechanical performance and inherent flame retardancy (EM Koch, H.-M. Walter, Kunststoffe 80 (1990) 1146; E. Doring, Kunststoffe 80, (1990) 1149; N. Inchaurondo-Nehm, Kunststoffe 2008 190). Polyarylene (ether) sulfones are generally known to those skilled in the art. In principle, for component A), any structure of polyarylene (ether) sulfone is encompassed by the present invention, provided that the polyarylene (ether) sulfone used as component A) has a viscosity number of less than 42 ml / g. It may be preferred that the viscosity number of component A) polyarylene (ether) sulfone is less than or equal to 41 ml / g, in particular less than or equal to 40 ml / g, and even more particularly less than or equal to 39 ml / g. According to a particular embodiment, the viscosity number of component A) polyarylene (ether) sulfone is less than or equal to 38 ml / g. According to a further embodiment, the polyarylene (ether) sulfone of component A) exhibits a viscosity number of less than 38 ml / g to 42 ml / g, in particular in the range of 38 ml / g to 41 ml / g.
[0014] Polyarylene (ether) sulfones are represented by the general formula II [ka] (Wherein, the symbols t, q, Q, T, Y, Ar and Ar 1 The definition is as follows: t and q are each independently 0, 1, 2 or 3; Q, T and Y are each independently a chemical bond or -O-, -S-, -SO2-, S=O, C=O, -N=N- and -CR a R b -, where R a and R b are each independently a hydrogen atom, (C1-C 12 ) Alkyl, (C1-C 12 )Alkoxy, (C3-C 12 ) cycloalkyl or (C6-C 18) an aryl group, where at least one of Q, T and Y is present and is -SO2-; Ar and Ar 1 are independent of each other, (C6~C 18 ) arylene It may be preferable in some cases for the unit to be composed of the following units:
[0015] Within the above preconditions, when Q, T or Y is a chemical bond, this means that the left adjacent group and the right adjacent group are directly linked to each other through a chemical bond.
[0016] According to one preferred embodiment, t and q are independently 0 or 1.
[0017] According to a preferred embodiment, Q, T and Y in formula II are independently a chemical bond, -O-, -SO2- and -CR a R b -, with the proviso that at least one of Q, T and Y is present and is -SO2-. a and R b are preferably, independently of each other, hydrogen or (C1-C4) alkyl.
[0018] -CR a R b - In R a and R b are preferably independently hydrogen, (C 12 ) Alkyl, (C1-C 12 )Alkoxy and (C6-C 18 ) aryl.
[0019] (C1-C 12 )Alkyl refers to a linear or branched saturated hydrocarbon group having 1 to 12 carbon atoms. The following moieties are included: (C1-C6)alkyl, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, 2- or 3-methylpentyl, and (C7-C 12) Alkyl, such as unbranched heptyl, octyl, nonyl, decyl, undecyl, lauryl, and their mono- or poly-branched analogs are specifically included.
[0020] "C1~C 12 The term "-alkoxy" refers to a straight or branched alkyl group having 1 to 12 carbon atoms attached via an oxygen at any position within the alkyl group, e.g., methoxy, ethoxy, n-propoxy, 1-methylethoxy, butoxy, 1-methyl-propoxy, 2-methyl-propoxy or 1,1-dimethylethoxy.
[0021] (C3~C 12 )Cycloalkyl refers to a monocyclic saturated hydrocarbon group having 3 to 12 carbon ring members, and specifically includes (C3-C8)cycloalkyl, such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclopropylmethyl, cyclopropylethyl, cyclopropylpropyl, cyclobutylmethyl, cyclobutylethyl, cyclopentylethyl, -propyl, -butyl, -pentyl, -hexyl, cyclohexylmethyl, -dimethyl and -trimethyl.
[0022] Ar and Ar 1 are independent of each other, (C6~C 18 According to a particular embodiment, Ar 1 is unsubstituted (C6-C 12 ) an arylene group.
[0023] Ar and Ar 1 are preferably independently selected from phenylene, bisphenylene and naphthylene groups, and arylene groups derived from anthracene, phenanthrene or naphthacene. For example, Ar and Ar 1is independently selected from 1,2-phenylene, 1,3-phenylene, 1,4-phenylene, 1,6-naphthylene, 1,7-naphthylene, 2,6-naphthylene and 2,7-naphthylene, 2,7-dihydroxynaphthylene and 4,4'-bisphenylene.
[0024] In particular, Ar and Ar 1 are independently selected from phenylene and naphthylene groups, for example, independently selected from 1,2-phenylene, 1,3-phenylene, 1,4-phenylene, 1,6-naphthylene, 1,7-naphthylene, 2,6-naphthylene and 2,7-naphthylene, and more particularly, independently selected from 1,4-phenylene, 1,3-phenylene and naphthylene. Furthermore, according to another embodiment of the present invention, Ar and Ar 1 are independently selected from arylene groups derived from anthracene, phenanthrene, or naphthacene. According to yet further embodiments, Ar and Ar 1 is independently selected from 2,7-dihydroxynaphthylene and 4,4'-bisphenylene.
[0025] It may be preferred that the polyarylene (ether) sulfone according to component A) comprises at least one of the following repeat units IIa to IIo: [ka] [ka]
[0026] In addition to the units IIa to IIo which may preferably be present, other repeating units are those in which one or more 1,4-phenylene units derived from hydroquinone are replaced by 1,3-phenylene units derived from resorcinol or naphthylene units derived from dihydroxynaphthalene.
[0027] Particularly preferred units of general formula II are units IIa, IIg and / or IIk. According to a particular embodiment, it is particularly preferred that component A) polyarylene (ether) sulfone is essentially composed of one type of unit of general formula II, said one type being particularly selected from IIa, IIg and IIk.
[0028] According to a preferred embodiment, component A) polyarylene(ether)sulfone is composed of repeating units where Ar is 1,4-phenylene, t is 1, q is 0, T is a chemical bond, and Y is SO. This polyarylene(ether)sulfone is also called polyphenylenesulfone (PPSU) (formula IIg).
[0029] According to a further preferred embodiment, component A) polyarylene(ether)sulfone is composed of repeating units where Ar is 1,4-phenylene, t is 1, q is 0, T is C(CH3)2 and Y is SO2. This polyarylene(ether)sulfone is also called polysulfone (PSU) (formula IIa).
[0030] According to an even more preferred embodiment, component A) polyarylene (ether) sulfone is composed of repeating units in which Ar is 1,4-phenylene, t is 1, q is 0, and T and Y are SO2. This polyarylene (ether) sulfone is also called polyether sulfone (PESU) (formula IIk).
[0031] For the purposes of this disclosure, abbreviations such as PPSU, PESU and PSU comply with DIN EN ISO 1043-1:2001.
[0032] The amount of component A) present in the composition of the present invention is from 15 to 90% by weight.
[0033] According to a preferred embodiment, the amount of component A) is 15-85% by weight, in particular 15-70% by weight, more particularly 15-65% by weight, even more particularly 15-60% by weight of the composition. More particularly, certain embodiments use 15-55% by weight, more particularly 15-50% by weight, even more particularly 15-45% by weight of component A). According to a very specific embodiment, the amount of component A) is 18-83% by weight. In a further preferred embodiment, the amount of component A) is 20-75% by weight, in particular 20-70% by weight, more particularly 20-65% by weight, even more particularly 20-60% by weight of the composition. A very specific embodiment of the invention uses 20-55% by weight, more particularly 20-50% by weight, even more particularly 20-45% by weight of component A). According to another preferred embodiment, the amount of component A) is 25-75% by weight, in particular 25-70% by weight, more particularly 25-65% by weight, even more particularly 25-60% by weight of the composition. A very particular embodiment of the invention uses 25-55% by weight, more particularly 25-50% by weight, even more particularly 25-45% by weight of component A). In certain cases, an amount of 25-40% by weight, more particularly 25-35% by weight of component A) may be preferred.
[0034] The weight-average molar mass M of the polyarylene(ether)sulfone A) of the present invention w is preferably 10 000 to 40 000 g / mol, more particularly 10 000 to 37 000 g / mol, in particular 12 000 to 35 000 g / mol, particularly preferably 14 000 to 33 000 g / mol, determined by gel permeation chromatography in dimethylacetamide as solvent against narrowly distributed polymethyl methacrylate as standard. The polyarylene (ether) sulfones A) used according to the invention have a VN of less than 42 ml / g. According to one embodiment, VN is equal to or less than 40 ml / g. According to a further embodiment, VN is equal to or less than 38 ml / g. VN is measured as a 1% by weight solution in N-methyl-2-pyrrolidone at 25 ° C according to ISO 1628.
[0035] The preparation processes leading to said polyarylene(ether)sulfones are known per se to the person skilled in the art and are described, for example, in "Encyclopedia of Polymer Science and Technology" by Herman F. Mark, 3rd Edition, Volume 4, 2003, chapter "Polsulfones", pages 2-8, and also in "Aromatic Polyethers" by Hans R. Kricheldorf in the Handbook of Polymer Synthesis, 2nd Edition, 2005, pages 427-443.
[0036] The synthesis of polyarylene (ether) sulfones can generally be carried out by polycondensation of suitable monomers in dipolar aprotic solvents at high temperatures (RN Johnson et al., J. Polym. Sci. A-1 5 (1967) 2375; JE McGrath et al., Polymer 25 (1984) 1827). In order to achieve a desired VN, the molecular weight of the polyarylene (ether) sulfone must be controlled, which can be done, for example, by monitoring the torque level during the condensation, requiring a calibration curve between the torque level in the reaction mixture and the corresponding final product. Furthermore, by using general knowledge on the adjustment of the molecular weight by using the appropriate stoichiometric ratio between the monomers during the polycondensation, the molecular weight can be controlled so that the required viscosity of the polyarylene (ether) sulfone is achieved (see, for example, McGrath et al., Polym. Eng. Sci. 17, 647 (1977)). In this case too, the molecular weight M n A correlation between VN and VN must be established.
[0037] The known polyarylene (ether) sulfones usually have halogen end groups, in particular -F or -Cl, or phenolic OH or phenolate end groups, which can be present as such or in reacted form, in particular in the form of -OCH3 end groups.
[0038] Particularly preferred is the reaction between at least one aromatic compound having two halogen substituents and at least one aromatic compound having two functional groups reactive towards said halogen substituents in an aprotic polar solvent and in the presence of anhydrous alkali metal carbonate, in particular sodium carbonate, potassium carbonate, calcium carbonate or mixtures thereof, very particularly preferably potassium carbonate.One particularly preferred combination is N-methyl-2-pyrrolidone as solvent and potassium carbonate as base.
[0039] The polyarylene(ether)sulfones as component A) preferably have either halogen end groups, in particular chlorine end groups, or etherified end groups, in particular alkyl ether end groups, which can be obtained by reaction of the OH or phenolate end groups, respectively, with a suitable etherifying agent.
[0040] Examples of suitable etherifying agents are monofunctional alkyl or aryl halides, such as C1-C6-alkyl chlorides, bromides or iodides, preferably methyl chloride, or benzyl chloride, bromide or iodide, or mixtures thereof. For the purposes of the polyarylene (ether) sulfones of component A), preferred end groups are halogen, in particular chlorine, alkoxy, in particular methoxy, aryloxy, in particular phenoxy or benzyloxy.
[0041] Component A) has Cl- or O-CH3- end groups and the content of OH or phenolate end groups is less than 0.05% by weight, as determined by potentiometric titration.
[0042] As component B), 5-80% by weight of graphite is used. Graphite is a form of carbon, as described, for example, in "Lehrbuch der anorganischen Chemie" [Textbook of inorganic chemistry], 40, 91st-100th editions, pp. 701-702, by AF Hollemann, E. Wiberg, N. Wiberg. Graphite is composed of planar carbon layers superimposed on one another. The graphite can be pulverized by milling. The graphite used can be of natural or synthetic origin and has a high crystallinity and a low level of impurities such as SiO2. The volume average particle size, which can be measured by laser scattering, is in the range of 0.1 μm to 500 μm, preferably in the range of 1 μm to 300 μm, more particularly 5 μm to 250 μm. Furthermore, the thickness of the graphite layer can be determined by electron microscopy. The thickness of the graphite layer, determined by electron microscopy, is in the range of 0.05 μm to 100 μm, preferably 0.1 to 50 μm. It is preferable to use graphite having a low content of particles with a volume average particle size of less than 5 μm, for example 5% or less of particles with a volume average particle size of 5 μm or less.
[0043] An example of a commercially available graphite that can be used as component B) in the composition of the invention is Timrex KS75 from Imerys. Details regarding the influence of the particle size and anisotropy of the graphite on the kneading and electrical properties of the compound are also known from the art (Derieth, T., Kunststoffe 8 / 2015, page 82).
[0044] For clarity, the graphite component B) used according to the invention is "standard" graphite, whether natural or synthetic. The graphite component B) is not expanded graphite or expandable graphite, sometimes called exfoliated graphite. Expandable graphite is produced from ordinary graphite, such as naturally occurring graphite, where standard graphite flakes are usually treated with an oxidizing acid, e.g. sulfuric acid or nitric acid, thereby forming a graphite intercalation product. Such products can expand under the influence of heat. According to the invention, the term "graphite" as component B) does not encompass expandable graphite or expanded graphite.
[0045] According to a preferred embodiment, the amount of component B) is 10-80% by weight, in particular 15-80% by weight, more particularly 20-80% by weight, even more particularly 25-80% by weight of the composition. More particularly, an embodiment uses 30-80% by weight, more particularly 35-80% by weight, even more particularly 40-80% by weight of component B). In a further embodiment, the amount of component B) is 45-80% by weight, in particular 50-80% by weight, even more particularly 55-80% by weight. A further detailed embodiment of the invention uses 10-75% by weight, more particularly 10-70% by weight, even more particularly 10-65% by weight of component B). According to another preferred embodiment, the amount of component B) is 10-75% by weight, in particular 15-70% by weight, more particularly 20-70% by weight, even more particularly 25-70% by weight of the composition. Very particular embodiments of the present invention use 30-70% by weight, more particularly 35-70% by weight, even more particularly 40-70% by weight of component B). In certain cases, an amount of 45-75% by weight, more particularly 50-70% by weight of component B) may be preferred.
[0046] The composition of the present invention comprises, as component C), 5-80% by weight of conductive carbon black. The conductive carbon black used can be any commonly used form of carbon black, and a variety of carbon blacks can be used, differing in structure, surface chemistry and wetting behavior. An example of a suitable product is Ketjenblack 300, available from Akzo. A further example of a suitable carbon black is Printex XE 2 from Orion Engineered Carbons. Printex® L by Orion Engineered Carbons or Ensaco 250 conductive carbon black from TimCal may also be suitable. Carbon black conducts electrons by means of graphite layers embedded in the amorphous carbon (F. Camona, Ann. Chim. Fr. 13, 395 (1988)). Electricity is conducted within and between aggregates of carbon black particles, if the distance between the aggregates is small enough. In order to obtain electrical conductivity while minimizing the loading, it is preferable to use carbon blacks with anisotropic structure (G. Wehner, Advances in Plastics Technology, APT 2005, Paper 11, Katowice 2005). In such carbon blacks, the primary particles associate to give an anisotropic structure, so that the necessary distance between the carbon black particles to achieve electrical conductivity is achieved in the compounded material even at relatively low loadings (C. Van Bellingen, N. Probst, E. Grivei, Advances in Plastics Technology, APT 2005, Paper 13, Katowice 2005). By way of example, the oil absorption (measured according to ASTM D2414-01) of suitable types of carbon black is at least 60 ml / 100 g, preferably more than 90 ml / 100 g. The BET (Brunauer-Emmett-Teller) surface area of suitable products is greater than 50 m 2 / g, preferably 60m 2 / g (measured by ASTM D3037-89). Various functional groups can be present on the surface of the carbon black. Conductive carbon black can be prepared by various processes (G. Wehner, Advances in Plastics Technology, APT 2005, Paper 11, Katowice 2005).
[0047] According to a preferred embodiment, the amount of component C) is 5-70% by weight, in particular 5-60% by weight, more particularly 5-50% by weight, even more particularly 5-40% by weight, more particularly 5-35% by weight of the composition. More particularly, an embodiment uses 6-70% by weight, more particularly 6-60% by weight, even more particularly 6-50% by weight of component C). In a further embodiment, the amount of component C) is 6-40% by weight. A more detailed embodiment of the invention uses 6-30% by weight, more particularly 6-25% by weight, even more particularly 6-20% by weight of component C). According to another preferred embodiment, the amount of component C) is 7-70% by weight, in particular 7-60% by weight, more particularly 7-50% by weight, even more particularly 7-40% by weight, more particularly 7-35% by weight of the composition.
[0048] The composition of the present invention comprises, as component D), 0 to 25% by weight, preferably 0 to 20% by weight, of carbon nanotubes. According to one embodiment of the present invention, the composition comprises carbon nanotubes in an amount of more than 0% to 25% by weight, preferably more than 0% to 20% by weight of component D).
[0049] Carbon nanotubes are carbon-containing nanoparticles in which carbon (predominantly) has a graphitic structure and the individual graphitic layers have a tubular arrangement. Nanotubes and their synthesis have been previously disclosed in the literature (e.g. J. Hu et al., Acc. Chem. Res. 32 (1999), 435-445). For the purposes of the present invention, in principle, any type of nanotube can be used. Carbon nanotubes suitable as component D) preferably have an average diameter in the range of 1-300 nm. They may be single-walled or multi-walled carbon nanotubes, the nanotubes being present individually or in bundles, for example in bundles with a hexagonal arrangement. The preparation of carbon nanotubes may be by catalytic chemical vapor deposition at ambient or elevated pressure, alternatively by the graphite spark technique in the presence or absence of a catalyst, or by the laser vapor deposition technique in the presence of a catalyst. Such techniques are described, for example, in Carbon, vol. 32, p. 569 (1994), Nature, vol. 354, p. 56 (1991), and Science, vol. 273, p. 483 (1996). In the case of multi-walled carbon nanotubes, the diameter is preferably 10-200 nm. The average length of the carbon nanotubes may, for example, be in the range of 1-1000 μm.
[0050] For the purposes of the present invention, multi-walled nanotubes (MWNTs) are preferred as component D). Suitable nanotubes can be purchased, for example, from Applied Sciences Inc and / or Hyperion Catalysis Int., Cambridge Mass. (USA). See also EP 205556, EP 969128, EP 270666, US 6,844,061, WO 01 / 89013, US 5,651,922 and US 5,643,502, WO 01 / 36536 and WO 00 / 68299. According to a preferred embodiment, the amount of component D) is 1-25% by weight, in particular 1-20% by weight, more particularly 1-15% by weight, even more particularly 1-10% by weight of the composition. More specifically, some embodiments use 5 to 25 wt. %, more specifically 5 to 20 wt. %, and even more specifically 5 to 15 wt. % of component D).
[0051] According to one particular embodiment, the composition according to the invention is free of component D) (0% by weight).
[0052] According to the invention, the composition comprises at least one additive (component E)) in an amount of 0-40% by weight, in particular 0-30% by weight, more particularly 0-20% by weight, even more particularly 0-10% by weight, for example 0-5% by weight. In one embodiment of the invention, the composition of the invention comprises at least one additive (component E)) in an amount of component E) of more than 0% to 40% by weight, preferably more than 0% to 30% by weight, more particularly more than 0% to 20% by weight. According to this embodiment, component E) may be preferably present in an amount of more than 0% to 15% by weight, in particular more than 0% to 10% by weight, more particularly more than 0% to 5% by weight.
[0053] If present, it may be preferred that the composition comprises 0.01 to 20% by weight, more particularly 1 to 20% by weight, of at least one additive E). It may be more preferred that E) is used in an amount of 0.01 to 15% by weight, for example 0.5 to 10% by weight. It may be even more preferred that the composition of the invention comprises 0.5 to 8% by weight of E).
[0054] The at least one additive may be selected from, for example, processing aids, pigments, stabilizers, impact modifiers, or may be a mixture of various additives. Other examples of conventional additives are oxidation retardants, agents that inhibit degradation caused by heat or ultraviolet light, lubricants and mold release agents, dyes, and plasticizers, which may be used alone or in any combination with any other additive.
[0055] Examples of oxidation retarders and heat stabilizers that can be added to the compositions of the present invention are halide salts of metals of group I of the periodic table of elements, such as sodium halide, potassium halide or lithium halide, examples being chloride salt, bromide salt or iodide salt.Zinc fluoride, zinc chloride can also be used.Sterephedinols, hydroquinones, substituted representatives of said groups, secondary aromatic amines, optionally in combination with phosphorus-containing acids, or their salts or mixtures of said compounds can also be used, preferably in concentrations up to 1% by weight.
[0056] Examples of UV stabilizers are various substituted resorcinols, salicylates, benzotriazoles and benzophenones, commonly used amounts of up to 2% by weight.
[0057] Examples of lubricants, release agents, the amount of which can generally be up to 2% by weight, preferably up to 1% by weight, are stearyl alcohol, alkyl stearates and stearamides, and also esters of pentaerythritol with long-chain fatty acids. Dialkyl ketones, such as distearyl ketone, can also be used. It may be preferred that the composition of the invention comprises 0.1 to 2% by weight, more preferably 0.1 to 1.75% by weight, particularly preferably 0.1 to 1.5% by weight, in particular 0.1 to 0.9% by weight of stearic acid and / or stearates. In principle, other stearic acid derivatives, such as esters of stearic acid, can also be used.
[0058] Stearic acid is preferably produced by hydrolysis of fats. The products thus obtained are usually mixtures of stearic acid and palmitic acid. These products therefore have a wide softening range, for example from 50 to 70°C, depending on the product composition. It may be preferable to use products with a stearic acid content of more than 20% by weight, particularly preferably more than 25% by weight. Pure stearic acid (more than 98% by weight) can also be used.
[0059] Furthermore, component E) can also contain stearates. Stearates can be prepared either by reaction of the corresponding sodium salt with a metal salt solution (e.g., CaCl2, MgCl2, aluminum salts) or by direct reaction of fatty acids with metal hydroxides (see, e.g., Baerlocher Additives, 2005). Typically, it is preferred to use aluminum tristearate.
[0060] Other possible additives are nucleating agents, an example being talc powder. Component E) may comprise one or more impact modifiers, which may be at least one impact-modifying rubber. Rubbers are generally crosslinkable polymers that have elastomeric properties at room temperature.
[0061] Preferred rubbers that increase the toughness of the composition usually have two important characteristics: they contain an elastomeric fraction with a glass transition temperature below -10°C, preferably below -30°C, and they contain at least one functional group capable of interacting with the polyarylene (ether) sulfone. Examples of suitable functional groups are carboxylic acid, carboxylic anhydride, carboxylic ester, carboxamide, carboximide, amino, hydroxyl, epoxy, urethane and oxazoline groups.
[0062] Generally preferred functionalized rubbers include those containing the following components: d1) 40 to 99% by weight of at least one α-olefin having 2 to 8 carbon atoms; d2) 0 to 50% by weight of a diene; d3) 0 to 45% by weight of at least one C1 to C6 of acrylic acid or methacrylic acid 12 - alkyl esters, or mixtures of esters of this type, d4) 0 to 40% by weight of at least one ethylenically unsaturated C2-C 20 Mono- or dicarboxylic acids or functional derivatives of acids of this type, d5) 1 to 40% by weight of at least one monomer containing an epoxy group, and d6) at least one monomer capable of free radical polymerization and functionalized polyolefin rubbers constructed from
[0063] Examples of suitable at least one α-olefin (d1) are ethylene, propylene, 1-butylene, 1-pentylene, 1-hexylene, 1-heptylene, 1-octylene, 2-methylpropylene, 3-methyl-1-butylene and 3-ethyl-1-butylene. Ethylene and propylene may be preferred.
[0064] Examples of suitable at least one diene monomer (d2) are conjugated dienes having 4 to 8 carbon atoms, such as isoprene and butadiene, non-conjugated dienes having 5 to 25 carbon atoms, such as 1,4-pentadiene, 1,4-hexadiene, 1,5-hexadiene, 2,5-dimethyl-1,5-hexadiene and 1,4-octadiene, cyclic dienes, such as cyclopentadiene, cyclohexadiene, cyclooctadiene and dicyclopentadiene, and also alkenylnorbornenes, such as 5-ethylidene-2-norbornene, 5-butylidene-2-norbornene, 2-methallyl-5-norbornene and 2-isopropenyl-5-norbornene, and tricyclodienes, such as 3-methyltricyclo[5.2.1.02·6]-3,8-decadiene, or mixtures thereof. 1,5-hexadiene, 5-ethylidenenorbornene and dicyclopentadiene are preferred. The diene content may generally be 0 to 50% by weight, preferably 0.5 to 50% by weight, particularly preferably 2 to 20% by weight, and more particularly preferably 3 to 15% by weight, based on the total weight of the olefin polymer.
[0065] Examples of suitable at least one ester (d3) are methyl, ethyl, propyl, n-butyl, isobutyl, 2-ethylhexyl, octyl and decyl acrylates and the corresponding methacrylates. Among these, methyl, ethyl, propyl, n-butyl and 2-ethylhexyl acrylates and methacrylates may be particularly preferred.
[0066] Instead of or in addition to the at least one ester (d3), the olefin polymer may also contain an acid-functional and / or potentially acid-functional monomer (d4) in the form of at least one ethylenically unsaturated mono- or dicarboxylic acid.
[0067] Examples of the at least one monomer (d4) are acrylic acid, methacrylic acid, the tertiary alkyl esters of these acids, in particular tert-butyl acrylate, and dicarboxylic acids, such as maleic acid and fumaric acid, and derivatives of these acids, and also their half esters.
[0068] For the purposes of the present invention, potentially acid-functional monomers are compounds which form free acid groups under the conditions of polymerization or during the incorporation of the olefin polymer into the composition. Examples of these are the anhydrides of dicarboxylic acids having 2 to 20 carbon atoms, in particular maleic anhydride, and the tertiary C1-C12-alkyl esters of the abovementioned acids, in particular tert-butyl acrylate and tert-butyl methacrylate. The ethylenically unsaturated dicarboxylic acids and anhydrides (d4) are represented by the following formulae III and IV: [ka] (In the formula, R 5 , R 6 , R 7 and R 8 are each independently H or C1-C6-alkyl. has.
[0069] The epoxy group-containing monomer d5 is represented by the following formulae V and VI [ka] (In the formula, R 9 , R 10 , R 11 and R 12 are each independently H or C1-C6-alkyl, m is an integer from 0 to 20, and p is an integer from 0 to 10. has.
[0070] R 5 ~R 12 may preferably be hydrogen, m may preferably be 0 or 1, and p may preferably be 1.
[0071] Preferred compounds (d4) and (d5) may be selected from maleic acid, fumaric acid and maleic anhydride, respectively, and alkenyl glycidyl ethers and vinyl glycidyl ethers, respectively.
[0072] Particularly preferred compounds of formulae III and IV, and V and VI, respectively, may be maleic acid and maleic anhydride, and acrylates and / or methacrylates, both containing epoxy groups, especially glycidyl acrylate and glycidyl methacrylate, respectively.
[0073] Particularly preferred at least one olefin polymer may be made from 49.9 to 98.9% by weight, in particular 59.85 to 94.85% by weight of ethylene, 1 to 50% by weight, in particular 5 to 40% by weight of esters of acrylic or methacrylic acid, and 0.1 to 20.0% by weight, in particular 0.15 to 15% by weight of glycidyl acrylate and / or glycidyl methacrylate, acrylic acid and / or maleic anhydride.
[0074] Particularly suitable functionalized rubbers may be selected from ethylene-methyl methacrylate-glycidyl methacrylate polymers, ethylene-methyl acrylate-glycidyl methacrylate polymers, ethylene-methyl acrylate-glycidyl acrylate polymers and ethylene-methyl methacrylate-glycidyl acrylate polymers, and any mixtures thereof.
[0075] Examples of other monomers (d6) are, for example, vinyl esters and vinyl ethers, and mixtures thereof.
[0076] The above polymers can be prepared by processes known per se or available to the person skilled in the art by application of general knowledge, for example by random copolymerization, preferably at high pressure and temperature.
[0077] The melt index of the copolymers may generally be from 1 to 80 g / min 10 min (measured at 190° C. and a 2.16 kg load).
[0078] Additionally, functionalized ethylene-α-olefin copolymers such as ethylene-propylene-grafted maleic anhydride or ethylene-1-butene-grafted maleic anhydride may also be used as impact modifiers in the compositions of the present invention.
[0079] Core-shell graft rubbers are another group of suitable impact modifiers that can be used according to the present invention. These are graft rubbers that can be prepared in emulsion and are composed of at least one hard component and one soft component. The hard component is usually at least one polymer with a glass transition temperature of at least 25°C, and the soft component is usually at least one polymer with a glass transition temperature of 0°C or less. These products generally have a structure made of a core (graft base) and at least one shell (graft), the structure being typically the result of the order of addition of the monomers. The soft component is generally derived from butadiene, isoprene, at least one alkyl acrylate, at least one alkyl methacrylate or at least one siloxane, and at least one other comonomer if desired. Suitable siloxane cores can be prepared, for example, starting from cyclic oligomeric octamethyltetrasiloxane or tetravinyltetramethyltetrasiloxane. These can be reacted, for example, with γ-mercaptopropylmethyldimethoxysilane in a ring-opening cationic polymerization, preferably in the presence of sulfonic acid, to obtain a soft siloxane core. At least one siloxane may also be crosslinked, for example, by carrying out the polymerization in the presence of at least one silane having at least one hydrolyzable group, such as halo or alkoxy, such as tetraethoxysilane, methyltrimethoxysilane or phenyltrimethoxysilane. Examples of at least one comonomer suitable for this purpose are styrene, acrylonitrile, and crosslinkable or graftable monomers having two or more polymerizable double bonds, such as diallyl phthalate, divinylbenzene, butanediol diacrylate or triallyl (iso)cyanurate. The hard components are generally derived from styrene, α-methylstyrene or copolymers thereof, where at least one comonomer may preferably be acrylonitrile, methacrylonitrile or methyl methacrylate.
[0080] It may be preferred that at least one core-shell graft rubber comprises a soft core and a hard shell, or a hard core, a first soft shell and at least one further hard shell, where the incorporation of at least one functional group, such as carbonyl, carboxylic acid, anhydride, amide, imide, carboxylic ester, amino, hydroxyl, epoxy, oxazoline, urethane, urea, lactam or halobenzyl, may be carried out by adding at least one suitably functionalized monomer, preferably during the polymerization of the final shell.
[0081] Examples of suitable functionalized monomers are maleic acid, maleic anhydride, half esters or diesters, or maleic acid, tert-butyl (meth)acrylate, acrylic acid, glycidyl (meth)acrylate and vinyloxazoline. The proportion of monomers having functional groups can generally be 0.1-25% by weight, but preferably 0.25-15% by weight, based on the total weight of the core-shell graft rubber. The weight ratio of the soft component to the hard component can generally be 1:9-9:1, but preferably 3:7-8:2.
[0082] Rubbers of this type are known per se or are available to the person skilled in the art by utilizing his general knowledge and are described, for example, in EP-A-208187.
[0083] Thermoplastic polyester elastomers are another group of suitable impact modifiers. For the purposes of the present invention, polyester elastomers are segmented copolyetheresters that may generally comprise long-chain segments derived from poly(alkylene) ether glycols and short-chain segments that may be derived from low molecular weight diols and dicarboxylic acids. Products of this type are known per se or available to those skilled in the art and are described, for example, in U.S. Pat. No. 3,651,014. Corresponding products are also commercially available under the trademarks Hytrel® (DuPont), Arnitel® (Akzo) and Pelprene® (Toyobo Co., Ltd.).
[0084] According to one particular embodiment, the composition of the invention is free of component E) (0% by weight).
[0085] In particular, one particular embodiment of the present invention comprises: A) 18 to 83% by weight of at least one polyarylene (ether) sulfone having a viscosity number of less than 42 ml / g; B) 10 to 75 weight percent graphite; C) 7 to 50% by weight of conductive carbon black; D) 0 to 25% by weight of carbon nanotubes; E) 0 to 40% by weight of at least one additive; A composition comprising: This relates to a composition, wherein the sum of the weight percentages of the components of the composition is 100 weight percent.
[0086] A further embodiment of the present invention comprises A) 15 to 79% by weight of at least one polyarylene (ether) sulfone having a viscosity number of less than 42 ml / g; B) 15 to 79 weight percent graphite; C) 5 to 50% by weight of conductive carbon black; D) 1 to 25% by weight of carbon nanotubes; E) 0 to 40% by weight of at least one additive; A composition comprising: This relates to a composition, wherein the sum of the weight percentages of the components of the composition is 100 weight percent.
[0087] A further embodiment of the present invention comprises A) 25 to 55% by weight of at least one polyarylene (ether) sulfone having a viscosity number of less than 42 ml / g; B) 40 to 70 weight percent graphite; C) 5 to 35% by weight of conductive carbon black; D) 0 to 25% by weight of carbon nanotubes; E) 0 to 30% by weight of at least one additive; A composition comprising: This relates to a composition, wherein the sum of the weight percentages of the components of the composition is 100 weight percent.
[0088] A further particular embodiment of the present invention comprises A) 15 to 90% by weight of at least one polyarylene (ether) sulfone having a viscosity number of less than 42 ml / g; B) 5 to 80 weight percent graphite; C) 5 to 80% by weight of conductive carbon black; D) 0 to 25% by weight of carbon nanotubes; E) 0 to 40% by weight of at least one additive; A composition comprising: This relates to a composition, wherein the sum of the weight percentages of the components of the composition is 100 weight percent.
[0089] A further embodiment of the present invention comprises A) 18 to 83% by weight of at least one polyarylene (ether) sulfone having a viscosity number of less than 42 ml / g; B) 10 to 75 weight percent graphite; C) 7 to 50% by weight of conductive carbon black; D) 0 to 25% by weight of carbon nanotubes; E) 0 to 40% by weight of at least one additive; A composition comprising: This relates to a composition, wherein the sum of the weight percentages of the components of the composition is 100 weight percent.
[0090] A still further embodiment of the present invention comprises A) 15 to 79% by weight of at least one polyarylene (ether) sulfone having a viscosity number of less than 42 ml / g; B) 15 to 79 weight percent graphite; C) 5 to 50% by weight of conductive carbon black; D) 1 to 25% by weight of carbon nanotubes; E) 0 to 40% by weight of at least one additive; A composition comprising: This relates to a composition, wherein the sum of the weight percentages of the components of the composition is 100 weight percent.
[0091] A still further embodiment of the present invention comprises A) 25 to 55% by weight of at least one polyarylene (ether) sulfone having a viscosity number of less than 42 ml / g; B) 40 to 70 weight percent graphite; C) 5 to 35% by weight of conductive carbon black; D) 0 to 25% by weight of carbon nanotubes; E) 0 to 30% by weight of at least one additive; A composition comprising: This relates to a composition, wherein the sum of the weight percentages of the components of the composition is 100 weight percent.
[0092] The composition can be prepared by processes generally known in the art. In particular, the composition of the present invention is obtained by melt-kneading each component. Those skilled in the art are familiar with melt-kneading per se. Therefore, the present invention also relates to a process for preparing a composition comprising A), B) and C), and, if applicable, any of the optional components defined herein, comprising ii) melt-kneading the components. For example, the composition can be prepared by extrusion. More particularly, the process comprises i) feeding the components into a melt-kneading device, and ii) melt-kneading the components.
[0093] More specifically, the components are fed into a melt mixing (= kneading) device such as an extruder (single or twin screw), a Brabender or Banburry mixer, or a kneader. In each melt mixing device, the components are mixed together. The formed composition can then be extruded.
[0094] After extrusion, the strands are typically cooled and pelletized to obtain pellets or granules.
[0095] The components of the compositions of the present invention can be added in any desired order. The order in which the individual components are charged to the mixing device can be varied, for example, any two or optionally three of the components can be premixed, or all of the components can be mixed together.
[0096] For the performance of the product, homogeneous mixing is important. To achieve this, a mixing time of 0.1 to 30 minutes is generally appropriate. The mixing is preferably carried out at a temperature of at least 300°C, preferably at least 350°C. According to one embodiment, the temperature during mixing is kept between 300°C and up to 420°C, more preferably between 310°C and 420°C, more particularly between 350°C and 420°C, in particular between 350°C and 380°C. Furthermore, after mixing, for example in an extruder, the resulting strands are usually cooled and can be further processed, for example pelletized.
[0097] Surprisingly, the compositions according to the invention show an excellent combination of mechanical properties and high electrical conductivity, making them particularly suitable for use in, for example, bipolar plates. In addition, the compositions according to the invention provide good chemical resistance, improved thermal conductivity and processability, which is important in the manufacture of bipolar plates for fuel cells or electrolysis units.
[0098] The compositions of the present invention can be advantageously used to manufacture fibers, films, foams or molded articles. According to a further aspect, the present invention relates to a fiber, film or molded article comprising the composition described herein.
[0099] Due to mechanical properties and good thermal and electrical conductivity, the composition of the present invention is generally particularly suitable for making parts for electrical or electronic equipment.Because the composition of the present invention has high temperature resistance and good chemical resistance, it is particularly suitable for making parts for electrical or electronic equipment that are exposed to high temperature and / or chemicals.These may be industrial items such as the vehicle section in automobiles or airplanes.
[0100] Generally, the compositions of the present invention are suitable for use in bipolar plates. Accordingly, a further aspect of the present invention relates to a bipolar plate comprising the composition described herein. EXAMPLES
[0101] The following examples provide further illustration of the present invention but are not intended to limit it.
[0102] Compounding was performed using a twin-screw extruder (Rheomex PTW 25 / 42p, ThermoFisher) and barrel temperatures were set to keep the melt temperature below 400° C. Molding of test samples was performed at a melt temperature of 410° C. and a mold temperature of 200° C.
[0103] The resistivity of the injection molded samples was measured at four different contact pressures (5, 10, 20 and 30 bar). For each contact pressure, four different currents (0.5 A, 1 A, 1.5 A, 2 A) were used and the required voltage was measured. The resistivity was determined as the slope of the best fit line. Mechanical testing was performed according to DIN EN ISO 178:2010+A1:2013 on a three-point bending machine (Instron 5565). For each compound, five specimens were tested.
[0104] The thermal conductivity was measured in accordance with DIN EN ISO 22007-4 using a NETZSCH LFA 457 MicroFlash. The thermal conductivity in the through-plane direction was determined.
[0105] The solution viscosity of the polyarylene (ether) sulfone was determined using a 0.01 g / ml solution in N-methyl-2-pyrrolidone at 25°C.
[0106] Component A1: As component A, a polyethersulfone PESU was used having a viscosity number of 49.0 ml / g. The product used contained 0.19% by weight of Cl end groups (elemental analysis) and 0.23% by weight of OCH3 end groups ( 1H-NMR) The amount of OH end groups was below the detection limit (<0.02 wt%).
[0107] Component A2: As component A, a polyethersulfone PESU was used having a viscosity number of 41.2 ml / g. The product used contained 0.26% by weight of Cl end groups (elemental analysis) and 0.34% by weight of OCH3 end groups ( 1 H-NMR) The amount of OH end groups was below the detection limit (<0.02 wt%).
[0108] Component A3: Polyphenylene sulfone PPSU having a viscosity number of 49.0 ml / g was used as component A. The amount of OH end groups was below the detection limit (<0.02 wt%).
[0109] Component A4: Polyphenylene sulfone PPSU having a viscosity number of 40.2 ml / g was used as component A. The amount of OH end groups was below the detection limit (<0.02% by weight).
[0110] Component B1: As component B, graphite Timrex KS75 from Imerys was used.
[0111] Component C1: As component C, carbon black Printex XE 2 from Orion Engineered Carbons was used.
[0112] [Table 1]
[0113] The compositions of the invention have a good combination of mechanical properties and low resistivity. Surprisingly, these compounds are superior to PPS compounds of the same composition (30 PPS / 63 graphite / 7 carbon black, cf.) in terms of thermal conductivity. Furthermore, the influence of the viscosity number of component A) on the overall properties of the composition is very surprising. For example, when using polyethersulfones with higher VN, the resistivity is very high (see V1, V5), making such compositions unsuitable for certain applications, such as use in bipolar plates.
Claims
1. A) 15 to 90% by weight of at least one polyarylene (ether) sulfone having a viscosity number of less than 42 ml / g; B) 5 to 80 weight percent graphite; C) 5 to 80% by weight of conductive carbon black; D) 0 to 25 wt. % carbon nanotubes; E) 0 to 40 wt. % of at least one additive; A composition comprising: A composition, wherein the sum of the weight percentages of the components of said composition is 100 weight percent.
2. The composition of claim 1 comprising 15 to 85 weight percent of component A).
3. The composition of claim 2 comprising 10 to 75 weight percent of component B).
4. The composition of claim 3 comprising 5 to 50 weight percent of component C).
5. The composition of claim 1 comprising 15 to 79 weight percent of component A).
6. The composition of claim 5 comprising 15 to 75 weight percent of component B).
7. The composition of claim 6 comprising 5 to 50 weight percent of component C).
8. The composition of claim 7 comprising 1 to 25 weight percent of component D).
9. 9. The composition according to any one of claims 1 to 8, wherein the viscosity number of component A) is in the range of 38 ml / g to 41 ml / g.
10. 10. The composition of any one of claims 1 to 9, wherein component A) is one or more of PPSU, PESU and PSU.
11. ii) melt-kneading the components 11. A process for the manufacture of a composition according to any one of claims 1 to 10, comprising:
12. 12. The process of claim 11, wherein the temperature during the melt-blending is at least 350°C.
13. A composition obtainable by the process according to claim 11 or 12.
14. 14. Use of a composition according to any one of claims 1 to 10 or 13 in the manufacture of a fibre, a film or a moulded article.
15. 14. Use of a composition according to any one of claims 1 to 10 or 13 in the manufacture of a bipolar plate.
16. 14. A fiber, film or molded article comprising the composition of any one of claims 1 to 10 or 13.
17. 14. A bipolar plate comprising the composition of any one of claims 1 to 10 or 13.